Achievements, challenges and opportunities for the microfinance market in Colombia (2011)
This article exposes economic benefits from funding space available for low income population in the country, by a comparison of characteristic elements fromGrameen Bank experience in relation to microcredit institutionalization in Colombia. The problem of microfinance is examined in the light of conventional economic analysis. Institutional environment elements are treated in various countries, and then a Colombian reviewis presented. Finally, a series of representative indicators of microcredit are explored. The assessed indicators suggest that there is space formicrocredit expansionwith profitable condition.